Boosting cancer immunotherapy by biomineralized nanovaccine with ferroptosis-inducing and photothermal properties. (5th December 2022) - Ma, Siyu; Liang, Xiao; Yang, Ning; Yang, Jie; Zhang, Jun; Pan, Xiuhua; Wei, Yawen; Liu, Zengyi; Shen, Qi
Abstract : The biomineralized nanovaccine with ferroptosis-inducing and photothermal properties boosted antitumor immunotherapy and exhibited satisfactory therapeutic effect for melanoma. Abstract : Until now, treatment of refractory tumors and uncontrolled metastasis by cancer immunotherapy has not yet achieved satisfactory therapeutic results due to the insufficient in vivo immune response. Here, we proposed the construction of a therapeutic cancer nanovaccine Fe@OVA-IR820 with ferroptosis-inducing and photothermal properties for boosting cancer immunotherapy. Fe 3+ ions were chelated inside the exogenous antigen ovalbumin (OVA) by biomineralization to form the nanovaccine, to which the photosensitizer IR820 was loaded by electrostatic incorporation. After intratumoral injection, in situ immunogenic cell death (ICD) was triggered as a result of Fe 3+ -dependent ferroptosis. Endogenous neoantigens and damage-associated molecular patterns (DAMPs) were released because of ICD and worked synergically with the exogenous OVA to provoke the immune response, which was further amplified by the photothermal effect after near-infrared irradiation. The enhanced recruitment and infiltration of T cells were observed and resulted in the suppression of the primary tumor. The therapeutic regiment that combined Fe@OVA-IR820 nanovaccine with cytotoxic T lymphocyte-associated protein 4 (CTLA-4) checkpoint blockade significantly boosted anti-cancer immunity and inhibited the growth of distal simulated metastases. Therefore, we proposed Fe@OVA-IR820 nanovaccine combined checkpoint blockade as a potential therapeutic strategy for melanoma treatment.